PUBLIC-PRIVATE PPARTNERSHIP MANAGEMENT IN RUSSIA - O. A. Yastrebov (Модернизация, инновация, развитие, 2016)
At present, main agency responsible for development of the institution of public-private partnership (PPP) in Russia is National PPP Center, a department of Vnesheconombank (VEB). Subjects of the Federation start forming their regional PPP centers (PPPRC). According to VEB scheme, PPPRC should be a subdivision of regional administration with two organs: the lower (working) one and a supreme one (consisting of higher regional officers and submitting to the head of the region). In order to make PPP management system more efficient, it is suggested that PPPRC working organ be formed as a joint-stock company with certain share of the state or (provisionally) as a public unitary enterprise. Risks specific for Russian regional PPP are discussed.